2014
DOI: 10.1146/annurev-publhealth-032013-182411
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Americans Have Shorter Life Expectancy and Worse Health Than Do People in Other High-Income Countries?

Abstract: Americans lead shorter and less healthy lives than people in other high-income countries. We review the evidence and explanations for these variations in longevity and health. Our overview suggests that the US health disadvantage applies to multiple mortality and morbidity outcomes. The American health disadvantage begins at birth and extends across the life-course, and it is particularly marked for American women and for regions in the US South and Midwest. Proposed explanations include differences in health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
147
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(151 citation statements)
references
References 88 publications
(119 reference statements)
0
147
1
3
Order By: Relevance
“…And a series of comparative research studies strongly suggests that social capital, social integration, and informal social control-in families, schools, communities, and neighbourhoods-are on average less developed and more unequally distributed in the US than in comparable nations; with areas of concentrated poverty and cumulative disadvantage in American cities exhibiting very serious levels of disorganisation and endemic social problems (Messner & Rosenfeld 1997;Avendano & Kawachi 2014;Darroch et al 2001;Banks et al 2010;38 Because it focused on parallel developments in the US and the UK, rather than contrasts between them, Garland (2001) said little about the role of America's distinctive political system in shaping penal policy. For a detailed discussion of that issue, see Garland (2010).…”
Section: Social Structure Social Organisation and Social Problemsmentioning
confidence: 99%
“…And a series of comparative research studies strongly suggests that social capital, social integration, and informal social control-in families, schools, communities, and neighbourhoods-are on average less developed and more unequally distributed in the US than in comparable nations; with areas of concentrated poverty and cumulative disadvantage in American cities exhibiting very serious levels of disorganisation and endemic social problems (Messner & Rosenfeld 1997;Avendano & Kawachi 2014;Darroch et al 2001;Banks et al 2010;38 Because it focused on parallel developments in the US and the UK, rather than contrasts between them, Garland (2001) said little about the role of America's distinctive political system in shaping penal policy. For a detailed discussion of that issue, see Garland (2010).…”
Section: Social Structure Social Organisation and Social Problemsmentioning
confidence: 99%
“…In countries such as Australia, the United Kingdom, and Canada, health expenditures represent about 10% of GDP; in the United States, this number is closer to 17% (The World Bank, 2015). Paradoxically, outcomes in the United States are worse than elsewhere (Avendano & Kawachi, 2014), a clear indicator that there is waste in the system. A recent study showed that older people with diagnosed chronic diseases face catastrophic health expenditure even in some of the wealthiest countries in Europe (Arsenijevic et al, 2016).…”
mentioning
confidence: 99%
“…This far exceeded the next highest spender, France, by 50% [1]. Yet despite this expenditure, the US reported poorer health outcomes comparatively, with shorter life expectancy and a greater prevalence of chronic conditions [2]. This raised several questions about the successes and failures of the healthcare system, and whether the various players in the system were getting the bang for their buck.…”
mentioning
confidence: 99%